2017
DOI: 10.1038/hortres.2017.9
|View full text |Cite
|
Sign up to set email alerts
|

Apple dwarfing rootstocks exhibit an imbalance in carbohydrate allocation and reduced cell growth and metabolism

Abstract: Apple dwarfing rootstocks cause earlier shoot termination and reduced root and shoot mass. To identify physiological factors responsible for rootstock-induced growth restriction, we compared vascular-enriched gene expression between two dwarfing rootstocks (‘M27’ and ‘M9’) and the vigorous rootstock ‘M793’ using RNA sequencing and quantitative reverse transcriptase PCR. Differentially expressed genes common to both dwarfing rootstocks belonged to five main biological processes: (1) primary metabolism, (2) cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 84 publications
6
67
0
Order By: Relevance
“…To further identify how MdWRKY9 induces this dwarfing phenotype, we measured the concentrations of the following four hormones that are believed to have roles in plant dwarfing: IAA, CTK, BR and GA. It is widely accepted that IAA, GA and CTK are key factors affecting apple dwarfing (Lockard & Schneider, ); changes in their synthesis, transportation and signaling can cause the dwarfing phenotype (Werner et al ., , ; Yang et al ., ; Foster et al ., ). However, we did not detect any significant differences in IAA, CTK and GA concentrations between transgenic lines and wild‐type control plants.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…To further identify how MdWRKY9 induces this dwarfing phenotype, we measured the concentrations of the following four hormones that are believed to have roles in plant dwarfing: IAA, CTK, BR and GA. It is widely accepted that IAA, GA and CTK are key factors affecting apple dwarfing (Lockard & Schneider, ); changes in their synthesis, transportation and signaling can cause the dwarfing phenotype (Werner et al ., , ; Yang et al ., ; Foster et al ., ). However, we did not detect any significant differences in IAA, CTK and GA concentrations between transgenic lines and wild‐type control plants.…”
Section: Discussionmentioning
confidence: 97%
“…Dwarfing rootstocks are widely used in modern apple production for high-density planting and efficient mechanical management of orchards. Despite their utility and a century of research, the underlying molecular mechanism that mediates plant dwarfing is unknown (Foster et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, peach trees growing on dwarfing rootstocks had a lower level of glucose and fructose in leaves [27]. Levels of glucose and fructose are much lower in apple scions on dwarfing rootstocks, although sucrose and galactose concentrations remain unchanged [28]. For temperate species, the lower soluble sugar levels in the above-ground portion of trees growing on dwarfing rootstocks during the late autumn and dormancy periods have been associated with the low availability of carbohydrate reserve that reduces vegetative growth in the following spring season [26,29].…”
Section: Discussionmentioning
confidence: 99%
“…In their later work, Lordan and his colleagues (2017) showed a higher ABA content in the xylem exudates of the dwarfing stocks (G.11 and B.9) as compared to that in the taller forms (B.72020 and G.814). At the same time, it was found that the activity of ABA gene response and biosynthesis was decreased in the dwarfing stocks (Foster et al, 2017).…”
Section: Introductionmentioning
confidence: 93%